2016
DOI: 10.1557/jmr.2016.41
|View full text |Cite
|
Sign up to set email alerts
|

Spatial localization of Mms6 during biomineralization of Fe3O4nanocrystals inMagnetospirillum magneticumAMB-1

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Recent work by Oestreicher et al has shown the localization of Mms6 in the magnetosome during the crystal growth, wherein it was found to be in direct contact with the crystals indicating its signicance in their formation. 16 Using in situ liquid cell High Angle Annular Dark Field-Scanning Transmission Electron Microscopy (HAADF-STEM), Kashyap et al reported the surface localization of ferric ions on the negatively charged Mms6 micelles, which forms an amorphous precursor phase to iron oxide, upon slow addition of NaOH. Further, in the presence of Mms6, nucleation was observed only on the Mms6 micelle surface and not in the bulk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Oestreicher et al has shown the localization of Mms6 in the magnetosome during the crystal growth, wherein it was found to be in direct contact with the crystals indicating its signicance in their formation. 16 Using in situ liquid cell High Angle Annular Dark Field-Scanning Transmission Electron Microscopy (HAADF-STEM), Kashyap et al reported the surface localization of ferric ions on the negatively charged Mms6 micelles, which forms an amorphous precursor phase to iron oxide, upon slow addition of NaOH. Further, in the presence of Mms6, nucleation was observed only on the Mms6 micelle surface and not in the bulk.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in vivo studies have shown that Mms6 is not involved in the nucleation, but only in the crystal growth. 16,17 The hydrophilic C-terminal domain of Mms6 plays a critical role in the formation of these particles. 9,11,18 m2Mms6, a synthetic C-terminal domain mutant of the wild type Mms6, does not template the formation of larger, uniform magnetite crystals.…”
Section: Introductionmentioning
confidence: 99%
“…[ 50 ] We observed variability in the crystals, where some appear more similar to those produced by wild type, which is consistent with evidence that Mms6 is only localized to a subset of magnetosomes. [ 94 ]…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the observations that similar species make the same crystal form and size and random mutagenesis changes the number of crystals per cell, but not their shape. [ 21,102 ] In addition, expression timing and checkpoint control during biogenesis has also been seen to be important [ 70,94 ] and magnetosome membrane proteins that control crystal nucleation and growth have interdependent and redundant functions. [ 30,45,51,103 ] Therefore, using one chasses to build different IONPs may require the mining of whole operons or MAIs, the balancing of multiple genes, control over membrane invagination, and temporal circuits for gene expression ordering.…”
Section: Discussionmentioning
confidence: 99%
“…To purify magnetosomes and prepare cell soluble and membrane fractions of M. magneticum AMB-1 (ATCC 700264), the protocol described in [33] was followed. To clone mms13 (amb0951 in M. magneticum AMB-1; [22]), genomic DNA from M. magneticum AMB-1 was obtained from the American Type Culture Collection (ATCC #700264).…”
Section: Methodsmentioning
confidence: 99%